2016
DOI: 10.1016/j.str.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Annotation of Ion Channel Structures by Molecular Simulation

Abstract: SummaryIon channels play key roles in cell membranes, and recent advances are yielding an increasing number of structures. However, their functional relevance is often unclear and better tools are required for their functional annotation. In sub-nanometer pores such as ion channels, hydrophobic gating has been shown to promote dewetting to produce a functionally closed (i.e., non-conductive) state. Using the serotonin receptor (5-HT3R) structure as an example, we demonstrate the use of molecular dynamics to ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(109 citation statements)
references
References 57 publications
8
101
0
Order By: Relevance
“…Importantly, recent structural and modelling work suggests that the bona fide open structure of pLGICs most likely resembles the open structures of GLIC and GluCl, rather than the much larger pore conformation of the cryo-EM structure of the zebrafish α1 GlyR bound to glycine alone (Gonzalez-Gutierrez et al 2017). A contrario, recent MD simulations suggest that the wide open zebrafish α1 GlyR structure is conductive, while the ivermectin-and glycine-bound α1 GlyR structure should not conduct ions (Trick et al 2016). In these simulations, however, it is unclear whether the simulated conduction properties of the wide-open zebrafish α1 GlyR match the experimentally derived values, nor is it possible to infer how much structural change is required to convert the ivermectinand glycine-bound α1 GlyR structure into a conductive conformation.…”
Section: The Detailed Analysis Of Picrotoxin Block Of Anionic Plgics mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, recent structural and modelling work suggests that the bona fide open structure of pLGICs most likely resembles the open structures of GLIC and GluCl, rather than the much larger pore conformation of the cryo-EM structure of the zebrafish α1 GlyR bound to glycine alone (Gonzalez-Gutierrez et al 2017). A contrario, recent MD simulations suggest that the wide open zebrafish α1 GlyR structure is conductive, while the ivermectin-and glycine-bound α1 GlyR structure should not conduct ions (Trick et al 2016). In these simulations, however, it is unclear whether the simulated conduction properties of the wide-open zebrafish α1 GlyR match the experimentally derived values, nor is it possible to infer how much structural change is required to convert the ivermectinand glycine-bound α1 GlyR structure into a conductive conformation.…”
Section: The Detailed Analysis Of Picrotoxin Block Of Anionic Plgics mentioning
confidence: 99%
“…A contrari o, recent MD simulations suggest that the wide open zebrafish α1 GlyR structure is conductive, while the ivermectin‐ and glycine‐bound α1 GlyR structure should not conduct ions (Trick et al . ). In these simulations, however, it is unclear whether the simulated conduction properties of the wide‐open zebrafish α1 GlyR match the experimentally derived values, nor is it possible to infer how much structural change is required to convert the ivermectin‐ and glycine‐bound α1 GlyR structure into a conductive conformation.…”
Section: Introductionmentioning
confidence: 97%
“…However, if these profiles suggest the channel may contain a hydrophobic gate or any other interesting features then a more in-depth analysis based on equilibrium MD simulation of the structure can be performed. Figure 2 is a crystal structure of a mammalian 5-HT 3 receptor (PDB ID: 4PIR) in which the existence of a hydrophobic gate has been demonstrated by previous studies (Trick et al, 2016;Yuan et al, 2016) . Initial structural analysis with CHAP (i.e.…”
Section: Workflow For 'Channotation' Of Pore Structuresmentioning
confidence: 87%
“…In a previous study we have shown how molecular dynamics (MD) simulations of water behaviour within these nanoscale structures can be used to aid this process (Trick et al, 2016) . Here we now present a new and highly versatile computational tool that implements this methodology to predict the conductive status of new ion channel structures.…”
Section: Introductionmentioning
confidence: 99%
“…Toolkits such as IBiSA_tools [247] may provide more detailed, centralized analyses of ion conduction, though they rely on at least brief independently generated molecular dynamics simulations. Automated simulation methods based on water permeation (as recently proposed by Sansom and colleagues [248]) may provide more accessible analyses, though the appropriate constraints and range of simulation models remain to be validated. All-atom molecular dynamics simulations of full conformational transitions associated with activation, permeation, desensitization, etc.…”
Section: Future Directions In Integrating Molecular Dynamics and Lmentioning
confidence: 99%